Pengaruh Tax Morale Dan Pemahaman Tri Nga Terhadap Peningkatan Kepatuhan Calon Wajib Pajak - Dewi Kusuma Wardani; Wahyu Anugrah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Compliance is a condition when the taxpayer completes all tax obligations and fulfills his taxation. This study aims to find out what are the effects of tax morale and tringa understanding on increasing taxpayer compliance. Quantitative description is the research method used as well as students in the Special Region of Yogyakarta as the population. Taking the selected method using the convenience sampling method. Social media is the platform chosen to disseminate as well as accommodate the data needed in this research. From the distribution of links through social media, 100 students were obtained as respondents. The results of the study show that tax morale has a positive effect on increasing the compliance of prospective taxpayers and understanding of the tri-nga has a positive effect on increasing the compliance of prospective taxpayers.